2021
DOI: 10.1093/mnras/stab2698
|View full text |Cite
|
Sign up to set email alerts
|

Star formation in CALIFA survey perturbed galaxies – II. Star-formation histories and oxygen abundances

Abstract: Galaxy evolution is generally affected by tidal interactions. Firstly, in this series, we reported several effects which suggest that tidal interactions contribute to regulating star formation (SF). To confirm that so, we now compare stellar mass assembly histories and SF look-back time annular profiles between CALIFA survey tidally and non-tidally perturbed galaxies. We pair their respective star-forming regions at the closest stellar mass surface densities to reduce the influence of stellar mass. The assembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Actually, even in galaxy pairs, both metallicity dilution and enrichment are found (Omori & Takeuchi 2022). In a study of CALIFA galaxies, the authors found that the oxygen abundances are only slightly lower in tidally perturbed galaxies than the control galaxies (Morales-Vargas et al 2021). These studies confirm the complexity of the physical processes imprinted on the gas-phase metallicity.…”
Section: Discussionmentioning
confidence: 77%
“…Actually, even in galaxy pairs, both metallicity dilution and enrichment are found (Omori & Takeuchi 2022). In a study of CALIFA galaxies, the authors found that the oxygen abundances are only slightly lower in tidally perturbed galaxies than the control galaxies (Morales-Vargas et al 2021). These studies confirm the complexity of the physical processes imprinted on the gas-phase metallicity.…”
Section: Discussionmentioning
confidence: 77%